Anatrophic Nehphrolithotomy: Preservation of Renal Function and Stone Clearance Rate - Naveed A. Mahar, Harris H. Qureshi, Ghulam M. Kalhoro, Riaz A. Laghari, Syed A. Shah, Maryam Saeed, Rehan Mohsen, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the outcomes of anatrophic nephrolithotomy in terms of stone clearance and change in renal function. Study design: Observational study Place and duration of study: Department of Urology Sindh Institute of Urology & Transplantation, Karachi from 1st January 2016 to 31st December 2021. Methodology: Fifty patients who underwent anatrophic nephrolithotomy from were enrolled. Outcomes were measured in terms of stone clearance, change in pre and post procedure eGFR, serum creatinine and differential renal function on renal scan (MAG-3 scan). Results: There were 30 (60%) males and 20 (40%) females with mean age was 5.96±13.09 years. Post-operative serum creatinine and eGFR were compared with pre-operative values and no statistically significant difference observed. Comparison of pre-operative and post-operative 99mTc-mercaptoacetyltriglycine (MAG3) scans revealed statistically significant mild loss of renal function with p-value of0.376. Conclusion: Anatrophic nephrolithotomy can be an alternative for multi tract PCNL when there is huge stone burden as it yields excellent stone clearance, and it can be practiced fearlessly for large staghorn stones because they can become the frequent cause of infections and mortality. Although parenchymal damage after anatrophic nephrolithotomy is of concern, renal dysfunction is usually clinically insignificant. Key words: Anatrophic nephrolithotomy, Staghorn stone, Renal calculi